BOX-BEHNKEN DESIGN-BASED DEVELOPMENT AND CHARACTERIZATION OF POLYMERIC FREEZE-DRIED NANOPARTICLES OF ISRADIPINE FOR IMPROVED ORAL BIOAVAILABILITY - GHOSE, DEBASHISH; PATRA, CHINAM NIRANJAN; SWAIN, SURYAKANTA; SRUTI, JAMMULA (International Journal of Applied Pharmaceutics, 2023)
Objective: This study aimed to develop and optimize isradipine-loaded polymeric freeze-dried nanoparticles prepared by solvent shifting method with the help of the experiment design for improving oral drug bioavailability and minimizing dosing intervals. Methods: Isradipine is a potent anti-hypertensive drug that is matrixed in polymeric freeze-dried nanoparticles using solvent shifting. In this work, a 3-factor, 3-level box-Behnken design was used to optimize the process parameters like a drug: PLA concentration (A), poloxamer 407 concentration (B), and stirring speed (C). In addition, responses were measured as dependent variables such as percentage drug release, particle size (nm), Zeta potential (mV), and % entrapment efficiency. Results: Mathematical equations and response surface plots were used to relate the dependent and independent variables. The optimization model exhibited 97.36 % drug release, 153.14 nm particle size,-25.9 mV Zeta potential, and 78.25% entrapment efficiency, respectively. The observed responses were in close agreement with the predicted values of the optimized process. Fourier transform infrared spectroscopy, morphological studies, and in vitro drug release studies characterized the prepared polymeric nanoparticles. Conclusion: The improved freeze-dried polymeric nanoparticle samples exhibited an in vitro drug release rate of more than 90% at 24h. Based on in vivo pharmacokinetic parameters, the isradipine-loaded polymeric nanoparticles show better bioavailability than pure drug's suspension form.